(untitled) (Conferencea, 2022)
There are relatively few lakes in Uzbekistan and they are uneven. Most of the lakes in the country are small and of local significance. Lakes in the territory of Uzbekistan are not the same in terms of the formation of cauldrons. However, most of them are lakes located in the river valleys in the plains. On the contrary, the lakes in the mountainous part of the republic are dams, moraines and tectonic lakes. Changes in the level of reservoirs in Uzbekistan depend on water demand. When water is not needed for agricultural crops, and especially during the spring floods, water accumulates in reservoirs and its level rises, while in the summer the collected water is used for irrigation and the water level decreases.